Green synthesis of silver nanoparticles with sintrong leaf infusion (Crassocephalum crepidioides) as antibacterial activity - I Wayan Tanjung Aryasa Aryasa; Putu Diah Darmayanti; Ni Putu Widayanti (Pharmaciana, 2026)
Substances with dimensions in the 1–100 nm range are categorized as nanoparticles. Physicochemical properties differ markedly from those of conventional bulk materials. Silver is particular interest for its well-documented antimicrobial capacity, which is greatly amplified when silver is reduced to nanoparticle size. AgNPs have been developed as effective agents for combating bacterial and fungal infections. Among available synthesis routes, green biosynthesis has gained prominence as a clean and sustainable option. It harnesses the reduction potential of plant-derived metabolites to produce nanoparticles without generating harmful waste. The antimicrobial efficacy of the synthesized AgNPs was assessed against Staphylococcus aureus and Escherichia coli via the agar diffusion method, and characterization was carried out using PSA and UV-Vis spectrophotometry at repeated intervals. PSA measurements indicated that raising AgNO₃ from 1 to 2 mM produced nanoparticles with average diameters of 63.1 nm and 52.0 nm, respectively. UV-Vis data collected from the first day showed an ascending then descending trend, with AgNP-characteristic absorption peaks in the 422–452 nm zone. Antibacterial testing produced distinct inhibition: zone diameters against Staphylococcus aureus were AgNPs 1 10.57 ± 0.02 mm, AgNPs 2 10.21 ± 0.35 mm, AgNPs 3 10.98 ± 0.20 mm, and AgNPs 4 11.02 ± 0.51 mm, while inhibition against Escherichia coli yielded AgNPs 1 8.93 ± 0.04 mm, AgNPs 2 8.80 ± 0.10 mm, AgNPs 3 9.07 ± 0.07 mm, and AgNPs 4 9.31 ± 0.43 mm. Overall, these data confirm the antibacterial potential of AgNPs biosynthesized from sintrong leaf infusion effectively inhibited both tested bacterial organisms.